The analysis of teachers’ perceptions of moral education curriculum - Zhang, Quankun; Saharuddin, Norzihani; Abdul Aziz, Nor Azni (Frontiers Media, 2022)
With the development of teachers’ psychological cognition, the moral education curriculum develops as per the changes in times. Currently, a resurgence of interest on studying teachers’ perceptions of the moral education curriculum has observed. This is because moral education curriculum of each country plays a unique role in the overall design of the country’s education curriculum. However, studies on teachers’ perceptions of the moral education curriculum are scarce, and no framework has been developed to guide the teaching and learning of teachers for the moral education curriculum for schools. The moral education curriculum serves as one of the main vehicles for value education, with teachers as direct executors. It can influence the overall development of the school system and long-term development of a country. Thus, in this paper, we reviewed current literature related to teachers’ perceptions of the moral education curriculum and developed future trends considering teachers’ perceptions of the moral education curriculum in improving existing moral education programs in a country. We identified a list of keywords related to moral education curriculum and teacher perceptions and relevant to the scope of this study. These keywords were used to search the articles from the Scopus and WoS studies. Overall, 32 papers meeting the search criteria were retrieved. Further, we conducted thematic studies, and four themes were successfully identified: the model of teacher perceptions of moral and national education, the dimensions of the teacher ethics model (framework), teaching strategies, and the role of teachers. The results of this study suggested a new framework for research trends in teachers’ perception models, particularly toward the moral education curriculum. This study contributed to the knowledge regarding teaching and learning approaches of moral education considering teachers’ perceptions of the moral education curriculum. The findings of study would benefit future studies and would improve the implementation of a country’s moral education program.